Faktor – Faktor Yang Mempengaruhi Profitabilitas Dan Dampaknya Terhadap Manajemen Laba - Agustina Agustina; Sulia Sulia; Rice Rice (Jurnal Akuntansi, 2018)
This study examine the influence of debt to equity ratio, firm size, institutional ownership, public ownership, independent board and audit committee on profitability and the impact for earning management. Populationfor this studywas 65 natural resource company listed in Indonesia Stock Exchange Period 2012-2015. Based on purposive sampling method, 21 natural resource company was selected (or 84 observation). Data was selected from the companies’ financial reports and analysed by using path analysis. This study found thatdebt to equity ratio, firm size, institutional ownership, public ownership, independent board and audit committee simultaneously affect profitability and earning management. Partialy, only independentboard affect profitability and only institutional ownership and public ownershipaffect earning management. Futhermore, profitability can only mediate the affect of institutional ownership, public ownership and independent board to earning management.